Particle suspension in the turbulent regime: the effect of impeller type and impeller/vessel configuration - Ibrahim, S.; Nienow, A.W. (1996)
Particle suspension in water has been studied using Rushton turbines, pitched blade turbines (pumping upwards and downwards), Chemineer HE3 and Lightnin A310 hydrofoils pumping downwards, and Ekato Intermig agitators. Flat and profiled bottoms have been used. The dimensionless parameter S, which is related to the minimum impeller speed for complete solids suspension based on the work of Zwietering, has been used to generalize the results for two different particles. The configuration requiring the lowest specific energy dissipation rate in the flat-bottomed tank was a downward- pumping impeller of 0.35 to 0.4 times the vessel diameter with a clearance off the base of 1/4 the vessel height. Under these conditions, the main flow pattern was such that the piles of solids associated with the regions of flow reversal at the periphery and of the centre of the base were both removed at about the same speed. By modifying the base to fill in these zones where solids collect, the minimum specific energy dissipation rate associated with this configuration using the HE3 hydrofoils could be further reduced by a factor of about 4 to 5. Compared to the HE3 hydrofoils, the Rushton turbines and the Intermigs required minimum specific energy dissipation rates for suspension 5 to 10 times higher at equivalent clearances and vessel base configurations.